Biodistribution of etoposide via intratumoral chemotherapy with etoposide-loaded implants - Chunsheng Wu; Xiangting Yi; Renzhi Xu; Maokuan Zhang; Yan Xu; Yan Ma; Li Gao; Zhengbao Zha (Taylor & Francis Group, 2020)
Etoposide (VP16) is the traditional antitumor agent which has been widely used in a variety of cancers. However, intravenous administration of VP16 was limited in clinical application because of its low aqueous solubility, poor bioavailability and dose-limiting adverse effects. Local chemotherapy with VP16-loaded drug delivery systems could provide a continuous release of drug at the target site, while minimizing the systemic toxicity. In this study, we prepared the poly-l-lactic acid (PLLA) based VP16-loaded implants (VP16 implants) by the direct compression method. The VP16 implants were characterized with regards to drug content, micromorphology, drug release profiles, differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) analyses. Furthermore, the biodistribution of VP16 via intratumoral chemotherapy with VP16 implants was investigated using the murine Lewis lung carcinoma model. Our results showed that VP16 dispersed homogenously in the polymeric matrix. Both in vitro and in vivo drug release profiles of the implants were characterized by high initial burst release followed by sustained release of VP16. The VP16 implants showed good compatibility between VP16 and the excipients. Intratumoral chemotherapy with VP16 implants resulted in significantly higher concentration and longer duration of VP16 in tumor tissues compared with single intraperitoneal injection of VP16 solution. Moreover, we found the low level of VP16 in plasma and normal organ tissues. These results suggested that intratumoral chemotherapy with VP16 implants enabled high drug concentration at the target site and has the potential to be used as a novel method to treat cancer.